Η διάχυση της εθνικής ταυτότητας στις ορθόδοξες κοινότητες της Κιλικίας - Εξερζόγλου Χάρης (Δελτίο Κέντρου Μικρασιατικών Σπουδών, 1995)
During the first decade of the 20th century the flourishing Greekorthodox communities in Cilicia were entangled in a bitter conflict with the Patriarchate of Antioch over the issue of the vacant metropolitan see of Adana and Tarsus. This conflict, although of ecclesiastical nature, became of critical importance in forging and diffusing a new form of collective identity in the area. Until the late 19th century religion was the dominant factor shaping the collective identity of the Greekorthodox communities in Ottoman Cilicia. Orthodoxy ensured the cohesion of these communities, despite their multilingual and multicultural character. The predominant language was Turkish although Arabic and Greek were also in use. Threats to the community’s cohesion were characteristically identified on the ground of religion. In this respect it was other Christian confessions, chiefly protestantism, that were regarded as the main challenges of orthodox identity. Thus both lay and ecclesiastical leaders directed their efforts against the prosyletizing zeal of western missions. The conflict with the Patriarchate of Antioch became the catalyst that shifted traditional allegiances and caused the Orthodox communities to undergo deep ideological changes. At first, these changes involved a new perception of the Patriarchate of Antioch. This old guardian of Orthodox Christianity came to be regarded as an Arab national institution which administered the church in violation of established practices and the Canon Law. Such a perception perhaps was not groundless, especially after the election of Meletios Dumani as Patriarch of Antioch in 1899. Hence the communities declined to accept clerics chosen by the Patriarch of Antioch for the metropolitan see of Adana and Tarsus and at a latter stage, demanded its secession from Antioch and its union with the Patriarchate of Constantinople. Through this conflict Orthodox communities came increasingly under the influence of nationalism. The once homogenous Orthodox community was now perceived in national terms and its members were divided along national lines, as «Arabs» and «Greeks». Though national definitions of belonging were only gradually accepted, they eventually prevailed National discourse proved an expedient language for expressing political demands but in the process existing criteria of collective identity were transformed. Cultural features such as language acquired a specific national meaning. Since language was acknowledged as part of national identity, the multilingual profile of the community became problematic. Linguistic fragmentation, a feature of no importance in the contex of a religious community, had to be accounted for and be dealt with Considering the multilingual environment of the community, it became difficult to promote the status of Greek language without resorting to specific measures. Thus links with national and educational societies in Greece were established to spread education in greek. Yet, shifts of meaning were not limited to language alone. History and perceptions of space were also reinterpreted in the same way. The complex nature of the Orthodox community was undermined by historical narratives and geographic references that laid emphasis on its national character and reinterpreted the history of the region accordingly. By underlining nationality as the bond of the community, these new interpretations attempted to establish links strong enough to detach, imaginatively, the Orthodox communities of Cilicia from their traditional perceptions of community and to link them with the Greek national community in the Ottoman Empire. Thus national discourse, despite its rather belated appeareance in relation to an issue of purely ecclesiastical nature, was succesful in redifining notions of collective identity and diffusing new understandings of community, language, history and education.